2021
DOI: 10.1007/s10753-021-01565-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of High Mobility Protein Group 1 and Interleukin-6 as Predictors of Outcomes Resulting from Variceal Bleeding in Patients with Advanced Chronic Liver Disease

Abstract: Variceal bleeding is a serious complication in cirrhotic patients and is related to increased expression of inflammatory mediators that accentuate circulatory dysfunction. The study aims to evaluate the performance of high mobility protein group 1 (HMG1) and interleukin-6 (IL-6) as predictors of acute kidney injury (AKI), infection and death in these patients. Fifty patients who were diagnosed with advanced chronic liver disease with variceal bleeding were included. The mean age was 52.8 ± 10.8 years, and 33 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On multivariable analysis, baseline HMGB1 was an independent predictor of AKI in HBV-ACLF patients after adjusting for all confounding factors. Multiple studies have shown that serum HMGB1 is predictive of the outcomes of end-stage liver and renal disease (Leelahavanichkul et al, 2011;Zhang et al, 2014;Dai et al, 2021;Dos Santos Pinheiro et al, 2022). Here, we showed that serum HMGB1 might be a prognostic biomarker for AKI among HBV-ACLF patients, while it was superior in the cirrhotic subgroup.…”
Section: Discussionmentioning
confidence: 55%
“…On multivariable analysis, baseline HMGB1 was an independent predictor of AKI in HBV-ACLF patients after adjusting for all confounding factors. Multiple studies have shown that serum HMGB1 is predictive of the outcomes of end-stage liver and renal disease (Leelahavanichkul et al, 2011;Zhang et al, 2014;Dai et al, 2021;Dos Santos Pinheiro et al, 2022). Here, we showed that serum HMGB1 might be a prognostic biomarker for AKI among HBV-ACLF patients, while it was superior in the cirrhotic subgroup.…”
Section: Discussionmentioning
confidence: 55%